Available feed resources, feeding practices and nutritional status of horses in Budgam district of Kashmir valley - HASSAN, SHABINA; GANAI, ABDUL MAJEED; BEIGH, YASIR AFZAL; FAROOQ, JAVID; KHAN, AZMAT ALAM; AHMAD, HAIDAR ALI; MASOOD, DANISH (The Indian Journal of Animal Sciences, 2018)
A study was conducted in four major horse rearing tehsils (Beerwah, Khag, Chadoora and Budgam) of district Budgam in Kashmir valley regarding available feed resources, feeding practices being followed and nutritional status of horses. Twelve equine keeping families from each study area were selected at random. The daily dry matter (DM), crude protein (CP), digestible energy (DE) and macro minerals (Ca and P) intakes by different classes of horses were calculated from the feed intakes and compared with the nutrient requirement given in the feeding standard. Adult horses were being fed rice straw, rice bran and wheat bran; however, in addition to these, bengal gram was fed in areas of Chadoora and Khag only, while maize grains was fed to the horses in Chadoora only. The horses were fed blend of spicy ingredients locally called as ‘masala’. None of the farmers offered any oil seeds/cakes, compound pelleted feed or mineral supplement to the horses, though, salt licks were allowed to the adult animals on daily basis in all the study areas. The chemical composition of all the feeds and fodders fed to horses in the study areas of district Budgam were within the ranges as prescribed for Indian feeds and fodders. While adult horses received optimum DM, the daily CP and DE intake was found to be deficient along with imbalanced Ca and P intake when compared to the standard requirements. Foals were found to get diets deficient in DM, DE, CP and Ca but surplus in P. Lactating mares received daily rations with optimum DM content, excess DE, slightly less CP and excessive Ca and P. It was concluded that the adult horses and lactating mares were being fed rations optimum in terms of quantity, but was not balanced in terms of nutrients; however, foals were fed diets deficient in both in quantity as well as quality.